Galvanising and fostering sub-national government leadership for area-wide sanitation programming. Issue 1 (6th January 2022) - Coultas, Mimi; Chanza, Mable Mideva; Iyer, Ruhil; Karangwa, Lambert; Kariuki, Jimmy Eric; Kosugi, Hodaka; Meeuwissen, Talia Timani; Mwende, Emmah; Myers, Jamie; Son, Philip; Ssemwanga, David Katwere
Abstract: Government leadership at both the national and sub-national levels is an essential step towards ensuring safely managed sanitation services for all. Though the importance of sub-national government leadership for water, sanitation and hygiene is widely acknowledged, to date much of the focus has been on the delivery of water services. This article sets out to start to address this imbalance by focusing on practical ways to galvanise and foster sub-national government leadership for sanitation programming. By focusing on the experiences across three sub-national areas in East Africa where positive changes in the prioritisation of sanitation by local governments have been witnessed, we (a group of researchers, local government representatives and development partner staff) cross-examine and identify lessons learnt. The results presented in this paper and subsequent discussion provide practical recommendations for those wishing to trigger a change in political will at the local level and create the foundation to strengthen sanitation governance and the wider system needed to ensure service delivery for all. HIGHLIGHTS: Operationalises systems strengthening thinking for sanitation and hygiene (S&H) at local government level. Draws lessons on supporting local governments to lead and prioritise S&H from three cases. Learning generated by local government and development partner staff from three countries. Makes practical recommendations on galvanising and fostering local government leadership and support for sanitation.